ADAPTATION LIBRARY VINNITSIA STATE MYKHAILO KOTSIUBYNSKYI PEDAGOGICAL UNIVERSITY TO THE REALITIES OF THE DIGITAL SPACE - Bilous, Valentina S. (University Library at a New Stage of Social Communications Development. Conference Proceedings, 2019)
The article reflects the innovative form of libraries, the development of the university libraries in the digital media space. The attention is focused on the experience of library in Vinnytsia State Pedagogical University.